Preparation method of liquid crystal synergistic high conductive silicone rubber composite material
By modifying the dispersion of conductive carbon black in the rubber matrix through biphenyl liquid crystal element structure material and improving the electronic transition capability, the problem of high resistivity of conductive silicone rubber is solved, and efficient conductivity and suitable flexible electromagnetic shielding are achieved. and temperature sensor parts.
Patent Information
- Application Number
- CN202311194561.5
- Authority / Receiving Office
- CN · China
- Patent Type
- Patents(China)
- Current Assignee / Owner
- Filing Date
- 2023-09-15
- Publication Date
- 2024-12-13
- Estimated Expiration
- 2043-09-15
AI Technical Summary
The existing conductive silicone rubber has a high resistivity and cannot be used for efficient flexible electromagnetic shielding and temperature sensor parts.
Modification of biphenyl liquid crystal primitive structure material, and the dispersion of conductive carbon black in the rubber matrix is improved through ultrasonic dispersion and mechanical blending, and the transition of electrons under temperature stimulation is enhanced through the conjugated structure of the liquid crystal primitive. ability.
It significantly reduces the resistivity of conductive rubber and improves the conductivity. It is suitable for efficient flexible electromagnetic shielding and temperature sensor parts.
Smart Images

Figure CN117304697B_ABST
Abstract
Description
Technical Field
[0001] The invention relates to the technical field of preparation of liquid crystal synergistic high-conductive silicone rubber composite materials, in particular to a preparation method of liquid crystal synergistic high-conductive silicone rubber composite materials. Background Art
[0002] Conductive rubber composite materials are widely used in the fields of flexible sensing and electromagnetic shielding materials due to their softness, low cost, flexibility, and easy processing. Silicone rubber has good high and low temperature resistance, excellent processing performance and mechanical properties, and unique chemical stability, and is usually used in harsh environments. However, the conductivity of ordinary silicone rubber is poor, and its conductivity can be significantly improved by adding conductive fillers. Commonly used conductive fillers are divided into two types: metal conductive fillers (such as silver powder, copper powder) and carbon conductive fillers (such as conductive carbon black, graphene, carbon nanotubes);
[0003] Most of the conductive silicone rubber currently sold on the market is made from acetylene carbon black, but its preparation process is relatively complicated, and the resistivity of the conductive rubber is still at a relatively high level and cannot be used for the development of efficient flexible electromagnetic shielding and temperature sensor devices.
[0004] Therefore, the present invention provides a method for preparing a liquid crystal-synergistic highly conductive silicone rubber composite material to solve the above-mentioned problems. Summary of the invention
[0005] Technical issues solved
[0006] In view of the shortcomings of the prior art, the present invention provides a method for preparing a liquid crystal synergistic high-conductive silicone rubber composite material. Based on the modification of the biphenyl liquid crystal unit structural material, the dispersion of conductive carbon black in the rubber matrix can be improved. At the same time, the conjugated structure of the liquid crystal unit can enhance the transition ability of electrons under temperature stimulation, and has the advantages of significant synergistic effect, etc., which solves the problem that the resistivity of the conductive rubber is still at a relatively high level and cannot be applied to the development of efficient flexible electromagnetic shielding and temperature sensor devices.
[0007] Technical Solution
[0008] In order to achieve the above-mentioned purpose of improving the dispersion of conductive carbon black in the rubber matrix, and at the same time, the conjugated structure of the liquid crystal unit can enhance the transition ability of electrons under temperature stimulation, and play a significant synergistic effect, the present invention provides the following technical solution: A method for preparing a liquid crystal synergistic high conductive silicone rubber composite material, comprising the following steps:
[0009] Step 1:
[0010] First, the intermediate 4,4′-di(β-hydroxyhexyloxy)biphenyl (BP6) was synthesized: 0.33 g of dihydroxybiphenyl was dissolved in 50 ml of ethanol with 6-chloro-1-hexanol at a molar ratio of 1:2, ultrasonically dispersed for 1 min, transferred to a three-necked flask, and sodium hydroxide solution was added dropwise under stirring. After the reaction was completed, the mixture was filtered and washed twice with deionized water, and dried to obtain the intermediate BP6;
[0011] Step 2:
[0012] Then, the synthesis of flexible liquid crystal polyurethane (FLCPU) was carried out based on step 1:
[0013] BP6 recrystallization: dissolve BP6 in a mixed solvent, heat and boil for 1-2 minutes, cool to room temperature to complete the first recrystallization, remove the supernatant, continue to add the above mixed solvent, heat and boil for 1-2 minutes, cool to room temperature to complete the second crystallization, and obtain the second recrystallized BP6 intermediate after drying;
[0014] Dissolve toluene diisocyanate (TDI) and BP6 in an appropriate amount of DMF in a ratio of (1.01-1.05):1, disperse by ultrasonic for 5 min-10 min, transfer to a three-necked flask, stir and drop 1-4% dibutyltin dilaurate, react at 90-100° C. for 20-28 h; filter to obtain a sample after cooling, rinse the sample with DMF 2-4 times, wash with deionized water 1-2 times, and dry to obtain a FLCPU sample;
[0015] Step 3:
[0016] VMQ and FLCPU are mixed by mechanical blending, and then conductive carbon black and dipentadienyl vulcanizing agent are added in sequence, and then FLCPU modified VMQ / CCB mixed rubber is obtained after 20-25 minutes; the mixed rubber is hot-pressed on a flat vulcanizer to obtain a finished product;
[0017] Step 4: Conduct material testing on the finished product of step 3 before and after modification and extract data.
[0018] Preferably, in the step 1, 40 ml of sodium hydroxide solution is added dropwise under stirring, and then the temperature is maintained at 90-100° C. and the reaction is continuously stirred for 8-10 hours. The rigid structural unit of the intermediate BP6 in the step 1 is one or more of a benzene ring, an alicyclic ring or a heterocyclic ring. Intermediates with core compositions of different rigidities can also achieve the expected effect of this experiment.
[0019] Preferably, the specification of the sodium hydroxide solution is 2-2.5 mol / L.
[0020] Preferably, when BP6 is recrystallized in step 2, the mixed solvent is prepared by mixing 90 ml of ethanol and 30 ml of N,N-dimethylformamide (DMF); before obtaining the sample, a small amount of deionized water is required for end-capping treatment for 2-3 hours.
[0021] Preferably, the diisocyanate in step 2 is any one of toluene diisocyanate (TDI) and hexamethylene diisocyanate (HDI).
[0022] Preferably, the hot pressing molding working conditions of the flat plate vulcanizer in step three are 170-175° C., lasting 5-10 min, and a pressure of 13-15 MPa.
[0023] Preferably, the mechanical blending method in step 3 includes any one or more of open mixing, internal mixing and extrusion, and the modified carbon black cannot be added into the rubber after the FLCPU liquid phase modified carbon black synthesized in the early stage;
[0024] The amount of the modifier FLCPU in the silicone rubber conductive carbon black system is controlled at 3-5%. The order of adding materials in step 3 must be to blend VMQ and FLCPU first, and then add conductive carbon black and other additives in sequence to ensure that the modification effect is achieved.
[0025] Preferably, the types of detection in step 4 include DSC detection, mechanical detection, scanning electron microscopy analysis and volume resistivity detection.
[0026] Beneficial Effects
[0027] Compared with the prior art, the present invention provides a method for preparing a liquid crystal-synergistic high-conductive silicone rubber composite material, which has the following beneficial effects:
[0028] 1. The preparation method of the liquid crystal synergistic high-conductive silicone rubber composite material is based on the modification of biphenyl-type liquid crystal unit structure materials, which can improve the dispersion of conductive carbon black in the rubber matrix. The intermediate BP6 can be replaced by a structure containing biphenyl or polycyclic aromatic hydrocarbons, which can also achieve the expected effect of this experiment, increase the raw material selection of the product, and improve the production efficiency of the product; and determine the amount of the modifier in the silicone rubber conductive carbon black system, and clarify that the FLCPU used for modification must be introduced into the rubber composite matrix in the form of mechanical open mixing, internal mixing, extrusion, etc., and the carbon black cannot be modified by the liquid phase of the previously synthesized FLCPU and then added to the rubber, highlighting the rigor and accuracy of the preparation method experiment.
[0029] 2. The preparation method of the liquid crystal synergistic high-conductive silicone rubber composite material can enhance the electron transition ability under temperature stimulation through the conjugated structure of the liquid crystal unit, and achieve a significant synergistic effect. BRIEF DESCRIPTION OF THE DRAWINGS
[0030] Figure 1 Schematic diagram of the synthesis of BP6 of the present invention;
[0031] Figure 2 It is a synthetic schematic diagram of FLCPU of the present invention;
[0032] Figure 3 Schematic diagram of DSC curves of BP6 and FLCPU synthesized in the present invention;
[0033] Figure 4 It is a schematic diagram of the mechanical stress-strain curve of the FLCPU modified VMQ / CCB vulcanizate of the present invention;
[0034] Figure 5 The cross-sectional SEM morphology of the VMQ / CCB composite material before and after FLCPU modification of the present invention;
[0035] Figure 6 This is a graph showing the change in volume resistivity of the VMQ / CCB composite material with temperature before and after FLCPU modification of the present invention. DETAILED DESCRIPTION
[0036] The following will be combined with the embodiments of the present invention to clearly and completely describe the technical solutions in the embodiments of the present invention. Obviously, the described embodiments are only part of the embodiments of the present invention, not all of the embodiments. Based on the embodiments of the present invention, all other embodiments obtained by ordinary technicians in this field without creative work are within the scope of protection of the present invention.
[0037] Embodiment 1:
[0038] A method for preparing a liquid crystal-synergistic high-conductive silicone rubber composite material comprises the following steps:
[0039] Step 1:
[0040] First, the intermediate 4,4′-di(β-hydroxyhexyloxy)biphenyl (BP6) was synthesized: 0.33 g of dihydroxybiphenyl was dissolved in 50 ml of ethanol with 6-chloro-1-hexanol in a molar ratio of 1:2, ultrasonically dispersed for 1 min, transferred to a three-necked flask, and sodium hydroxide solution was added dropwise under stirring. After completion, the mixture was filtered and washed twice with deionized water, and dried to obtain the intermediate BP6. 40 ml of sodium hydroxide solution was added dropwise under stirring, and then the temperature was maintained at 100°C and the reaction was stirred for 10 h. The specification of the sodium hydroxide solution was 2.5 mol / L, and the rigid structural unit of the intermediate BP6 in step 1 was a heterocycle. Intermediates with different rigid core compositions can also achieve the expected effect of this experiment.
[0041] Step 2:
[0042] Then, the synthesis of flexible liquid crystal polyurethane (FLCPU) was carried out based on step 1:
[0043] BP6 recrystallization: BP6 was dissolved in a mixed solvent, heated and boiled for 2 minutes, cooled to room temperature to complete the first recrystallization, the supernatant was removed, the above mixed solvent was continued to be added, heated and boiled for 2 minutes, cooled to room temperature to complete the second crystallization, and the second recrystallized BP6 intermediate was obtained after drying. When BP6 was recrystallized, the mixed solvent was prepared by mixing 90 ml of ethanol and 30 ml of N, N-dimethylformamide (DMF); before obtaining the sample, a small amount of deionized water was used for end-capping treatment for 3 hours;
[0044] Toluene diisocyanate (TDI) and BP6 were dissolved in an appropriate amount of DMF in a ratio of 1.05:1, ultrasonically dispersed for 10 minutes, transferred to a three-necked flask, stirred and 4% dibutyltin dilaurate was added dropwise, and reacted at 100°C for 28 hours; after cooling, the sample was filtered to obtain a sample, and then the sample was rinsed with DMF 4 times, washed with deionized water 2 times, and dried to obtain a FLCPU sample, wherein the diisocyanate was toluene diisocyanate (TDI);
[0045] Step 3:
[0046] VMQ and FLCPU are mixed by mechanical blending, and then conductive carbon black and dipentadienyl vulcanizing agent are added in sequence, and then FLCPU modified VMQ / CCB rubber compound is obtained after 25 minutes; the rubber compound is hot-pressed on a flat vulcanizer to obtain a finished product, the hot-pressing working conditions of the flat vulcanizer are 175°C, lasting for 10 minutes, and a pressure of 15 MPa, the mechanical blending method is open mixing, and the amount of the modifier FLCPU in the silicone rubber conductive carbon black system is controlled at 5%;
[0047] The order of adding materials in step 3 must be to blend VMQ and FLCPU first, and then add other additives such as conductive carbon black in sequence to ensure that the modification effect is achieved;
[0048] Step 4: Conduct material testing on the finished product of step 3 before and after modification, and extract data;
[0049] The types of tests include DSC testing, mechanical testing, scanning electron microscopy analysis and volume resistivity testing.
[0050] Embodiment 2:
[0051] A method for preparing a liquid crystal-synergistic high-conductive silicone rubber composite material comprises the following steps:
[0052] Step 1:
[0053] First, the intermediate 4,4′-di(β-hydroxyhexyloxy)biphenyl (BP6) was synthesized: 0.33 g of dihydroxybiphenyl was dissolved in 50 ml of ethanol with 6-chloro-1-hexanol in a molar ratio of 1:2, ultrasonically dispersed for 1 min, transferred to a three-necked flask, and sodium hydroxide solution was added dropwise under stirring. After completion, the mixture was filtered and washed twice with deionized water, and dried to obtain the intermediate BP6. 40 ml of sodium hydroxide solution was added dropwise under stirring, and the temperature was maintained at 90°C and stirred for 8 h. The specification of the sodium hydroxide solution was 2 mol / L, and the rigid structural unit of the intermediate BP6 in step 1 was a benzene ring. Intermediates with different rigid core compositions can also achieve the expected effect of this experiment.
[0054] Step 2:
[0055] Then, the synthesis of flexible liquid crystal polyurethane (FLCPU) was carried out based on step 1:
[0056] BP6 recrystallization: BP6 was dissolved in a mixed solvent, heated and boiled for 1 min, cooled to room temperature to complete the first recrystallization, the supernatant was removed, the above mixed solvent was continued to be added, heated and boiled for 1 min, cooled to room temperature to complete the second crystallization, and the second recrystallized BP6 intermediate was obtained after drying. When BP6 was recrystallized, the mixed solvent was prepared by mixing 90 ml of ethanol and 30 ml of N, N-dimethylformamide (DMF); before obtaining the sample, a small amount of deionized water was used for end-capping treatment for 2 h;
[0057] Toluene diisocyanate (TDI) and BP6 were dissolved in an appropriate amount of DMF in a ratio of 1.01:1, ultrasonically dispersed for 5 minutes, transferred into a three-necked flask, stirred and 1% dibutyltin dilaurate was added dropwise, and reacted at 90°C for 20 hours; after cooling, the sample was filtered to obtain a sample, and then the sample was rinsed with DMF twice, washed with deionized water once, and dried to obtain a FLCPU sample, wherein the diisocyanate was hexamethylene diisocyanate (HDI);
[0058] Step 3:
[0059] VMQ and FLCPU are mixed by mechanical blending, and then conductive carbon black and dipentadienyl vulcanizing agent are added in sequence, and then FLCPU modified VMQ / CCB rubber compound is obtained after 20 minutes; the rubber compound is hot-pressed on a flat vulcanizer to obtain a finished product, the hot-pressing working conditions of the flat vulcanizer are 170°C, lasting for 5 minutes, and a pressure of 13 MPa, the mechanical blending method is banburying, and the amount of the modifier FLCPU in the silicone rubber conductive carbon black system is controlled at 3%;
[0060] The order of adding materials in step 3 must be to blend VMQ and FLCPU first, and then add other additives such as conductive carbon black in sequence to ensure that the modification effect is achieved;
[0061] Step 4: Conduct material testing on the finished product of step 3 before and after modification, and extract data;
[0062] The types of tests include DSC testing, mechanical testing, scanning electron microscopy analysis and volume resistivity testing.
[0063] Embodiment three:
[0064] A method for preparing a liquid crystal-synergistic high-conductive silicone rubber composite material comprises the following steps:
[0065] Step 1:
[0066] First, the intermediate 4,4′-di(β-hydroxyhexyloxy)biphenyl (BP6) was synthesized: 0.33 g of dihydroxybiphenyl was dissolved in 50 ml of ethanol with 6-chloro-1-hexanol at a molar ratio of 1:2, ultrasonically dispersed for 1 min, transferred to a three-necked flask, and sodium hydroxide solution was added dropwise under stirring. After the end, the mixture was filtered and washed twice with deionized water, and the intermediate BP6 was obtained after drying. 40 ml of sodium hydroxide solution was added dropwise under stirring, and the temperature was maintained at 95°C and the reaction was continued with stirring for 9 h. The specification of the sodium hydroxide solution was 2 mol / L, and the rigid structural unit of the intermediate BP6 in step 1 was an alicyclic ring. Intermediates with core compositions of different rigidities can also achieve the expected effect of this experiment.
[0067] Step 2:
[0068] Then, the synthesis of flexible liquid crystal polyurethane (FLCPU) was carried out based on step 1:
[0069] BP6 recrystallization: BP6 was dissolved in a mixed solvent, heated and boiled for 1 min, cooled to room temperature to complete the first recrystallization, the supernatant was removed, the above mixed solvent was continued to be added, heated and boiled for 2 min, cooled to room temperature to complete the second crystallization, and the second recrystallized BP6 intermediate was obtained after drying. When BP6 was recrystallized, the mixed solvent was prepared by mixing 90 ml of ethanol and 30 ml of N, N-dimethylformamide (DMF); before obtaining the sample, a small amount of deionized water was used for end-capping treatment for 2 h;
[0070] Toluene diisocyanate (TDI) and BP6 were dissolved in an appropriate amount of DMF in a ratio of 1.04:1, ultrasonically dispersed for 8 minutes, transferred to a three-necked flask, stirred and 3% dibutyltin dilaurate was added dropwise, and reacted at 90°C for 24 hours; after cooling, the sample was filtered to obtain a sample, and then the sample was rinsed with DMF 3 times, washed once with deionized water, and dried to obtain a FLCPU sample, wherein the diisocyanate was toluene diisocyanate (TDI);
[0071] Step 3:
[0072] VMQ and FLCPU are mixed by mechanical blending, and then conductive carbon black and dipentadienyl vulcanizing agent are added in sequence, and then FLCPU modified VMQ / CCB rubber compound is obtained after 24 minutes; the rubber compound is hot-pressed on a flat vulcanizer to obtain a finished product, the hot-pressing working conditions of the flat vulcanizer are 173°C, lasting for 7 minutes, and a pressure of 14 MPa, the mechanical blending methods are open mixing and internal mixing, and the amount of the modifier FLCPU in the silicone rubber conductive carbon black system is controlled at 4%;
[0073] The order of adding materials in step 3 must be to blend VMQ and FLCPU first, and then add other additives such as conductive carbon black in sequence to ensure that the modification effect is achieved;
[0074] Step 4: Conduct material testing on the finished product of step 3 before and after modification, and extract data;
[0075] The types of tests include DSC testing, mechanical testing, scanning electron microscopy analysis and volume resistivity testing.
[0076] Test results:
[0077] DSC curve of FLCPU
[0078] Figure 3 It is the DSC curve of synthesized BP6 and FLCPU. In the figure, 98.4℃ and 175.7℃ represent the melting point Tm and the isotropic transition point (i.e. the clearing point Ti of the liquid crystal structure) of the crystalline structure in BP6 respectively. Similarly, 70.7℃ and 127.2℃ represent the melting point of the crystalline structure and the clearing point of the liquid crystal phase transition in the FLCPU synthesized with BP6 as the structural unit respectively, indicating that the synthesized flexible PU has typical liquid crystal structural characteristics, and its liquid crystal temperature range is in the range of 70-130℃;
[0079] Mechanical properties of materials before and after FLCPU modification
[0080] Figure 4 This is the mechanical stress-strain curve of the FLCPU-modified VMQ / CCB composite material. As can be seen from the figure, with the increase of FLCPU content in the system, the tensile stress of the material first increases and then decreases, and the elongation at break first decreases and then increases. When 4% FLCPU is added, the tensile stress of the composite material is significantly increased, the tensile strength is effectively maintained, and the comprehensive mechanical properties are significantly improved;
[0081] SEM analysis of FLCPU composites before and after modification
[0082] Figure 5This is a schematic diagram of the dispersion of carbon black in the silicone rubber matrix before and after PU modification. As can be seen from the figure, the size of carbon black aggregates is reduced after PU modification, and the dispersion of carbon black in the rubber matrix is significantly improved. This is beneficial to the improvement of the mechanical and electrical properties of the composite material;
[0083] Changes in volume resistivity of composite materials before and after FLCPU modification
[0084] Figure 6 The figure shows the change of volume resistivity of VMQ / CCB composite materials with temperature before and after FLCPU modification, and the corresponding values are shown in Table 1. As can be seen from the figure, the resistivity of the modified materials at the same temperature is significantly reduced, showing good conductivity enhancement characteristics, indicating that the improvement of carbon black dispersion after PU modification is conducive to the reduction of the overall resistivity of the material; at the same time, with the continuous increase of temperature, the composite material shows an obvious negative temperature coefficient effect, which is attributed to the fact that heating improves the transition ability of electrons in the system and improves the conductivity of the material. In addition, the rate of decrease of the volume resistivity of the modified material with increasing temperature is significantly stronger than that of the unmodified system, showing a higher linear fitting slope value, which indicates that the conjugated structure of the liquid crystal helps the migration of free electrons on the surface of carbon black in the system and improves the conductivity of the material. Further observation of Table 1 shows that, when the temperature exceeds 80°C, the volume resistivity of the composite material decreases from more than 40% in the low temperature zone to more than 60% compared with the unmodified system. This high temperature zone is in the liquid crystal phase transition zone, which fully demonstrates the role of liquid crystal in improving the conductivity of the overall material and proves the significant effect of the conjugated structure of the liquid crystal unit in guiding or assisting the free electron migration of carbon black.
[0085] Volume resistivity of VMQ / CCB composites before and after FLCPU modification at different temperatures
[0086]
[0087] The beneficial effects of the present invention are as follows: the preparation method of the liquid crystal synergistic high-conductive silicone rubber composite material can improve the dispersion of conductive carbon black in the rubber matrix based on the modification of biphenyl type liquid crystal unit structural materials, and the intermediate BP6 can be replaced by a structure containing biphenyl or polycyclic aromatic hydrocarbons, which can also achieve the expected effect of the experiment, increase the raw material selection of the product, and improve the production efficiency of the product; and determine the amount of the modifier in the silicone rubber conductive carbon black system, and clarify that the FLCPU used for modification must be introduced into the rubber composite material matrix in the form of mechanical open mixing, internal mixing, extrusion, etc., and the carbon black cannot be modified by the liquid phase of the FLCPU synthesized in the early stage, and then the modified carbon black is added into the rubber, highlighting the rigor and accuracy of the preparation method experiment; at the same time, the conjugated structure of the liquid crystal unit can enhance the transition ability of electrons under temperature stimulation, and play a significant synergistic effect.
[0088] Although embodiments of the present invention have been shown and described, it will be appreciated by those skilled in the art that various changes, modifications, substitutions and variations may be made to the embodiments without departing from the principles and spirit of the present invention, and that the scope of the present invention is defined by the appended claims and their equivalents.
Claims
1. A method for preparing a liquid crystal-synergistic highly conductive silicone rubber composite material, characterized in that: The following steps are involved: Step 1: First, the intermediate 4,4′-di-β-hydroxyhexyloxybiphenyl BP6 was synthesized: 0.33 g of dihydroxybiphenyl was dissolved in 50 ml of ethanol with 6-chloro-1-hexanol at a molar ratio of 1:2, ultrasonically dispersed for 1 min, transferred to a three-necked flask, and sodium hydroxide solution was added dropwise under stirring. After the addition, the mixture was filtered and washed twice with deionized water, and dried to obtain the intermediate BP6; Step 2: Then, the synthesis of flexible liquid crystal polyurethane FLCPU is carried out based on step 1: BP6 recrystallization: dissolve BP6 in a mixed solvent, heat and boil for 1-2 minutes, cool to room temperature to complete the first recrystallization, remove the supernatant, continue to add the above mixed solvent, heat and boil for 1-2 minutes, cool to room temperature to complete the second crystallization, and obtain the second recrystallized BP6 intermediate after drying; Dissolve toluene diisocyanate TDI and BP6 in an appropriate amount of DMF in a ratio of (1.01-1.05):1, disperse by ultrasonic for 5 min-10 min, transfer to a three-necked flask, stir and drop 1-4% dibutyltin dilaurate, react at 90-100°C for 20-28 h; cool and filter to obtain a sample, rinse the sample with DMF 2-4 times, wash with deionized water 1-2 times, and dry to obtain a FLCPU sample; Step 3: VMQ and FLCPU are mixed by mechanical blending, and then conductive carbon black and dipentadienyl vulcanizing agent are added in sequence, and then FLCPU modified VMQ / CCB mixed rubber is obtained after 20-25 minutes; the mixed rubber is hot-pressed on a flat vulcanizer to obtain a finished product; Step 4: Conduct material testing on the finished product of step 3 before and after modification and extract data.
2. The method for preparing a liquid crystal-synergistic highly conductive silicone rubber composite material according to claim 1, characterized in that: In the step 1, 40 ml of sodium hydroxide solution is added dropwise under stirring, and then the temperature is maintained at 90-100° C. and the stirring is continued for 8-10 hours.
3. The method for preparing a liquid crystal synergistic high conductive silicone rubber composite material according to claim 2, characterized in that: The specification of the sodium hydroxide solution is 2-2.5 mol / L.
4. The method for preparing a liquid crystal-synergistic highly conductive silicone rubber composite material according to claim 1, characterized in that: When BP6 is recrystallized in step 2, the mixed solvent is prepared by mixing 90 ml of ethanol and 30 ml of N,N-dimethylformamide (DMF); before obtaining the sample, a small amount of deionized water is required for end-capping treatment for 2-3 hours.
5. The method for preparing a liquid crystal-synergistic highly conductive silicone rubber composite material according to claim 1, characterized in that: The hot pressing molding working conditions of the flat plate vulcanizer in step 3 are 170-175° C., lasting 5-10 minutes, and a pressure of 13-15 MPa.
6. The method for preparing a liquid crystal-synergistic high-conductive silicone rubber composite material according to claim 1, characterized in that: The mechanical blending method in step 3 includes any one or more of open mixing and internal mixing, and the amount of FLCPU in the high conductive silicone rubber composite material is controlled at 3-5%; the order of adding materials in step 3 must be that VMQ and FLCPU are blended first, and then other additives are added in sequence to ensure that the modification effect is achieved.
7. The method for preparing a liquid crystal-synergistic highly conductive silicone rubber composite material according to claim 1, characterized in that: The types of detection in step 4 include DSC detection, mechanical detection, scanning electron microscope analysis and volume resistivity detection.
